Transient Inhibition of mTORC1 Signaling Ameliorates Irradiation-Induced Liver Damage - Yang, Wuping; Shao, Lijian; Zhu, Sihong; Li, Huan; Zhang, Xinxin; Ding, Congcong; Wu, Xincheng; Xu, Rui; Yue, Mengzhen; Tang, Jiahui; Kuang, Bohai; Fan, Guangqin; et al. (Frontiers in Physiology, 2019)
Despite radiotherapy is often used to treat liver cancer with recurrence after surgery, irradiation-induced liver damage cannot be ignored. It has documented that activation of TGF-β and NF-κB signaling pathways plays important roles in irradiation-induced liver pathologies. However, the significance of mTOR signaling remains undefined after irradiation exposure. In the present study, we investigated the effects of inhibiting mTORC1 signaling on the irradiated livers. Male C57BL/6J mice were acutely exposed to 8.0 Gy of x-ray total body irradiation and subsequently treated with rapamycin. The effects of rapamycin treatment on irradiated livers were examined at days 1, 3 and 7 after the exposure. The results showed that 8.0 Gy of irradiation resulted in hepatocyte edema, hemorrhage and sinusoidal congestion along with the decrease of ALB expression. Exposure of mice to irradiation significantly activated mTORC1 signaling pathway determined by pS6 and p-mTOR expression via western blot and immunostaining. Consistently, transient inhibition of mTORC1 signaling by rapamycin treatment accelerated liver recovery from irradiation, which was evidenced by decreasing sinusoidal congestion and increasing ALB expression after irradiation. The protective role of rapamycin on irradiated livers might be mediated by decreasing cellular apoptosis and increasing autophagy. These data suggest that transient inhibition of mTORC1 signaling by rapamycin protects livers against irradiation-induced damage.